High-Density Lipoprotein and Heart Failure - Liyun Xing; Yixuan Liu; Jiayu Wang; Peiqing Tian; Ping Liu (Reviews in Cardiovascular Medicine, 2023)
The protective effect of high-density lipoprotein (HDL) on atherosclerosis is well known, and its mechanisms of action has been extensively studied. However, the impact of HDL on heart failure and its mechanisms are still controversial or unknown. The cardioprotective role of HDL may be reflected in its antioxidant, anti-inflammatory, anti-apoptotic, and endothelial function protection. In epidemiological studies, high-density lipoprotein cholesterol (HDL-C) levels have been negatively associated with heart failure (HF). The major protein component of HDL-C is apolipoprotein (Apo) A-I, while paraoxonase-1 (PON-1) is an essential mediator for many protective functions of HDL, and HDL may act through components like (Apo) A-I or PON-1 to delay heart failure progress. HDL can slow heart failure disease progression through parts like (Apo) A-I or PON-1. The potential causality between HDL and heart failure, the role of HDL in the pathogenesis of HF, and its interaction with C-reactive protein (CRP), triglycerides (TG), and monocytes in the process of heart failure have been briefly summarized and discussed in this article. HDL plays an important role in the pathogenesis, progression and treatment of HF.